HASIL BELAJAR BIOLOGI MENGGUNAKAN LISTENING TEAM DISERTAI TALKING STICK DITINJAU DARI KEMAMPUAN AWAL SISWA KELAS VIII SMP NEGERI 1 JATEN TAHUN PELAJARAN 2010/2011 - Rinawati, Rinawati; Rosyidi, Alvi; Probosari, Riezky Maya (Pendidikan Biologi, 2011)
ABSTRACT ? The purposes of this research were to know: 1) the influence of implementing Listening Team method accompanied Talking Stick toward student?s achievement at SMP Jaten, 2) the influence of student?s starting ability toward achievement of biologi at SMP Jaten, 3) the interaction between teaching method and student?s starting ability toward achievement of biology at SMP Jaten, 4) the influence of a greater teaching method between conventional  teaching method and Listening Team method accompanied Talking Stick toward achievement of biology. This research wasquasiexperimental research using Randomized Control Only Design. The teaching method and the student?s starting ability were independent variable and the achievement of biology wasdependent variable. The population of this research wasthe VIII grade of SMP Negeri 1 Jaten on 2 nd semester, in the academic year 2010/2011. The sample of this research wereclass VIII-D as the experimentalclass and class VIII-F as the control class. Technique of collecting the achievement of biology data used documentary technique and test. While technique of analyzing the data used two ways anova which continued by further test using Bonferroni method to find out the level of treatment influence. The conclusion of this research were: 1) there was the significant influence of implementing Listening Team Method accompanied Talking Stick toward student?s achievement of biology in SMP Negeri 1 Jaten, 2) therewas the significant influence of student?s starting ability toward achievement of biology in SMPNegeri 1 Jaten, 3) there wasn?tinteraction between teaching method and student?s starting ability toward achievement of biology in SMP Negeri 1 Jaten, 4) based on further test Listening Team method accompanied Talking Stick is greater teaching method than convensional method. Keywords: Study achievement, Biology, Listening Team, Talking Stick, Starting ability